Implementasi Customer Relationship Management (CRM) Berbasis Website Pada Kantor Advokat Jou H Waimahing & Associates - Rhosita Ina Khadija; Carolina Ety Widjayanti; Endang Setyawati (Mahesa Research Institute, 2021)
Therefore, an a-based information system is needed website that is useful for connecting and matching potential clients with the right legal consultants with easier access without having to come directly to the office. The purpose of this system is to improve legal services to facilitate access to legal consulting services for the community, besides that, it can establish sustainable good relationships between legal consulting services offices and clients, another term can be called Customer Relationship Management (CRM). The benefit of implementing this CRM is that the company can know what the clients expect and need so that it can create a relationship and there is good two-way communication between the legal consultant and the client. In this case, the system development method uses the method prototype model. Based on the results of the -***benefits test, the average value of usability is 96.67%, learnability is 98%, efficiency is 98%, and acceptability is 96.63%. These results have been above the average value of at least 75%, so it can be concluded that the system built can be applied and used to facilitate access to legal consulting services for the community and all functions in the system function properly.